Dynamic colour change in the lizard Pelturagonia nigrilabris and P. spiniceps from Borneo. - Hayden R., Davis; Kyra S., Woytek; Izneil, Nashriq; Aaron M., Bauer; Indraneil, Das (Societas Europaea Herpetologica, 2022)
The communication presents first record of colour change in two Bornean endemic species of agamid lizards, Pelturagonia nigrilabris and P. spiniceps.